Selective dissolution of woody biomass under hydrothermal conditions. (December 2017) - Hernández O., Jesús D.; Tran, Khanh-Quang; Trinh, Thuat T.
Abstract: This study analyzes semi-continuous hydrothermal hydrolysis of lignocellulosic biomass operating between 200°C and 300°C with constant inlet water flow rate. Experiments were executed in a novel reactor system that offered a nearly linear temperature behavior during the heating period with heating rates between 40°C/min and 60 °C/min and a nearly flat temperature profile during retention. Experimental results suggest that conversion efficiency improved at higher temperatures. After completion of the batch, solid and liquid products were collected and mass balance closures reached an average of 89%. It was discovered that, regardless of the temperature, a minimum of 90% of the total dissolution occurs within the first 15 minutes of the reaction. This work identifies various stages and conditions that favor the dissolution of certain components (hemicellulose, cellulose or lignin).